Estudo para obtenção de bio-óleo de 2ª geração através da pirólise de plantas aquáticas - Santos, Luana Oliveira dos (2013)
The need for energy is increasing rapidly directed by increased industrialization and population growth beyond environmental issues. So has focused for obtaining energy from renewable sources such as biomass. The production of 2nd generation biofuels from this feedstock, through the thermal conversion process, has been a viable alternative due to its natural availability, which can be converted into liquid, solid and gaseous biofuels. One potential source of biomass is the water hyacinth, due to its high rate of uncontrolled growth, which has affected various water bodies. Thus this paper proposes a microscale studies to evaluate the thermal conversion into liquid biofuel of Eichhornia crassipes (EC), Eichhornia azurea (EA) and Nymphaea spp. (Ny), aquatic plants present in River Poxim and Weir Macela around Aracaju-SE and Itabaiana-SE. The biomasses were characterized for moisture content, oil content, ash content, thermal gravimetric analysis (TGA), infrared (IR), elemental analysis and Fluorescence Spectrometry X-ray Energy Dispersive (EDX). The bio-oil product from micropyrolysis at 525 ± 10 °C was trapped in actived charcoal being tested as eluting solvents dichloromethane, acetonitrile, tetrahydrofuran and methanol. The solvent that showed the best extraction capacity was tetrahydrofuran. As the polar characteristic of chemical constituents, solutions of bio-oils have been subjected to derivatization with MSTFA, seeking help identify components through their silanes derivatives. The plants had high moisture content between 90-93%, oil content of 6.0% and 2.6% for EA and EC respectively. The ash content for EA, EC and Ny were 14.5, 19.2 and 13.0%, respectively. According to the TGA curve from 41% to 47% of weight loss can be attributed to the decomposition of hemicellulose and cellulose (184-390 °C) and 71% to 72.6% is attributed to lignin degradation (390-590 °C), leaving 18.5% (EA), 21.4% (EC) and 24.5% (Ny) of ash and charcoal. The IR spectra of biomasses showed absorption band in the region of 3000-3600 cm-1 which is attributed to stretching of the binding of alcohols and / or phenols, absorptions in the region 3000-2800 cm-1 typical of aliphatic and bands in C-H 1560-1575 cm-1 related to C=C vibration of aromatics. The composition of bio-oils showed predominantly the presence of oxygenates, aromatics (phenols), and aliphatic (fatty acids), being the main compounds found the 2-furanemethanol, 1,2-benzenediol, hexadecanoic acid. Preliminary studies indicate the possibility of conversion of biomass to bio-oil. Pyrolysis of EC at low temperature (300 °C) gave a yield of 14.39% bio-oil, 77.98% biochar and 7.63% of biogas.